Análise de três dimensões do Programa Minha Casa Minha Vida: Expansão Urbana, infraestrutura de saneamento e emprego - Hiromoto, Martha Hanae (2018)
This thesis studies the largest Brazilian Housing Program Minha Casa Minha Vida - PMCMV. Initially, using the Faixa 1 Housing Program data and satellite images, the analyzes investigates literature critics to the housing estates location. Does PMCMV cause urban sprawl? The results suggest that PMCMV has contributed to the new urban development, once it induces leapfrog, a kind of urban spaces occupancy beyond the urban fringe, areas that generally have deficient provision of services and urban infrastructure. In addition, it has also been found that the Program fails to occupy the inner empty urban spaces. Municipalities where the Program contract more UH tend to infill less empty urban spaces than their peers with less or no UH contracted. As a result of the evidence of the Program’s precarious location, we analyze, more specifically, the provision of sanitation infrastructure in municipalities with a higher proportion of HU contracts over their household inventory. Has the Program worsened the water and sewage network? The results indicate that municipalities where there is a higher proportion of UH contracts, decrease their indicators of water network coverage and sewage collection. These data corroborate the results of distant location of the first study, indicating that the Program has placed the low income population far from the urban centers, in worst locations served by urban sanitation infrastructure. Lastly, given the Program’s failures evidences to provide an adequate social housing policy, as it has not placed the needy population close to urban centers, with all the services these places can offer, we examine whether its “secondary” objective of local economy development, has produced positive results. This last study shows that, in the localities with the highest proportion of UH (of all Faixas 1, 2, 3 ) on the stock of households, there is an increase in the level of employment, both general and civil construction, as well as an increase in the level of average wages. So, the Program works much more as an instrument of economic development than as a housing policy. The results indicate that the largest housing program in Latin America serves much more to the construction and real estate sector than the population lacking adequate housing.